Amine functionalized magnetic resorcinol formaldehyde as a green and reusable nanocatalyst for the Knoevenagel condensation - Paria Dehghani; Dawood Elhamifar; Shiva Kargar (Scientific Reports)
Abstract Herein, a novel amine-functionalized magnetic resorcinol-formaldehyde with a core-shell structure (Fe3O4@RF/Pr-NH2) is prepared through the chemical immobilization of (3-aminopropyl)trimethoxysilane over Fe3O4@RF composite. Characterization through FT-IR, EDX, PXRD, and TGA confirmed successful surface modification while preserving the crystalline structure of Fe3O4. The VSM analysis demonstrated excellent superparamagnetic properties, and SEM and TEM images revealed spherical particles for the designed nanocatalyst. The Fe3O4@RF/Pr-NH2 nanocomposite was employed as a robust nanocatalyst to promote the Knoevenagel condensation of benzaldehydes with ethyl cyanoacetate and malononitrile, resulting in the formation of substituted olefins. Various aromatic aldehydes were used as substrates in the presence of 0.01 g of Fe3O4@RF/Pr-NH2, achieving high to excellent yields (87–97%) within short reaction times (10–50 min) in EtOH at 60 °C. The high performance of Fe3O4@RF/Pr-NH2 is attributed to the hydrophobic nature of RF shell, which facilitates the accumulation of organic precursors around the catalytic active sites and enhances product yields. The designed magnetic catalyst could retain its high efficiency for at least ten runs. The metal-free, low-cost, and environmentally friendly attributes of the Fe3O4@RF/Pr-NH2 catalyst make it a promising alternative to traditional metal-based catalysts.